1987
DOI: 10.1007/bf00331596
|View full text |Cite
|
Sign up to set email alerts
|

Retardation of cell cycle progression in yeast cells recovering from DNA damage: A study at the single cell level

Abstract: Pedigree analyses of individual yeast cells recovering from DNA damage were performed and time intervals between morphological landmark events during the cell cycle (bud emergence and cell separation), were recorded for three generations. The associated nuclear behavior was monitored with the aid of DAPI staining. The following observations were made: All agents tested (X-rays, MMS, EMS, MNNG, nitrous acid) delayed the first bud emergence after treatment, which indicates inhibition of the initiation of DNA rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…It has been suggested that delay of bud emergence after DNA damage may be due to active inhibition of DNA replication during periods of extensive DNA repair (Wintersberger & Karwan, 1987). In our experiments, prototrophic diploid cells treated with 50 µl EMS first showed evidence of normal budding after 14 h of growth whereas normal budding of treated haploid cells was not apparent until after transfer to fresh YPD medium i.e.…”
Section: (B) Ca Eatsmentioning
confidence: 67%
See 1 more Smart Citation
“…It has been suggested that delay of bud emergence after DNA damage may be due to active inhibition of DNA replication during periods of extensive DNA repair (Wintersberger & Karwan, 1987). In our experiments, prototrophic diploid cells treated with 50 µl EMS first showed evidence of normal budding after 14 h of growth whereas normal budding of treated haploid cells was not apparent until after transfer to fresh YPD medium i.e.…”
Section: (B) Ca Eatsmentioning
confidence: 67%
“…We chose the mutagen EMS for study because it has been extensively studied in yeast (Loprieno, 1966 ;Nasim & Auerbach, 1967 ;Prakash & Sherman, 1973 ;Prakash & Higgins, 1982 ; see also Kilbey & Hunter, 1983 ;Schiestl & Wintersberger, 1983 ;van Zeeland et al, 1983 ;Orthen et al, 1984 ;e.g. reviewed by Sega, 1984 ;Wintersberger & Karwan, 1987 ;Klein et al, 1989 ;Klein et al, 1990 ;Lee et al, 1992). EMS is an alkylating agent that causes DNA damage ; repair of this damage induces a high frequency of G\C to A\T transition mutations in yeast (Prakash & Sherman, 1973 ;Sega, 1984 ;Kohalmi & Kunz, 1988 ;Lee et al, 1992).…”
Section: Introductionmentioning
confidence: 98%
“…Exposure of yeast cells to ionizing radiation or methyl methanesulfonate causes growing cells to arrest in G 2 . Arrested cells retain large buds and a single undivided nucleus (55,71,80,82). Initial experiments established that rad9 strains were deficient in DNA damageinduced cell cycle arrest (80), and additional genes were subsequently identified (71).…”
mentioning
confidence: 99%
“…The cessation of DNA replication triggered by DNA damage has been demonstrated in Escherichia coli (3). Additionally, several studies indicate that a variety of DNA-damaging agents inhibit DNA replication in yeast (4). However, it is not known whether this response requires an active regulatory process or is exclusively the result of the passive stalling of replicative and/or transcriptional complexes at sites of base damage.…”
mentioning
confidence: 99%